Expansion Deformation Law and Deterioration Mechanism of Expansive Soil in Guangxi under Different Initial Water Content - ZHAO Erping; TANG Jialin; LI Zhikun; ZHANG Cong (Renmin Zhujiang)
In order to study the influence of initial water content on expansion deformation and strength deterioration of expansive soil after water absorption, a formula for expansion deformation of expansive soil considering the influence of initial water content was constructed. Expansive soil in Guangxi Province was selected as the research object, and expansion tests and mechanical property tests of expansive soil under different initial water content conditions were carried out. The expansion deformation characteristics, structure, and strength deterioration law of expansive soil were studied, and the expansion softening mechanism of expansive soil was revealed. The results show that the soil expansion process can be divided into three stages: rapid expansion, slow expansion, and stable expansion. The maximum expansion rate decreases gradually with the increase in initial water content during stable expansion. The expansion coefficient of soil after water absorption decreases exponentially with the increase in initial water content and finally tends to be stable. The formula for expansion deformation considering the influence of initial water content can better simulate the expansion process of soil samples under different initial water content conditions. With the increase in the initial water content, the water absorption during soil expansion increases first and then decreases. Expansion due to water absorption makes pores in soil change from small and medium sizes to micro and small sizes; the pore area increases, and the strength decreases. After hydrophilic minerals in the soil absorb water, the unit cells become larger, and the distance between the unit cells becomes larger. In addition, the number of overlapping particles becomes smaller, and the binding mode between soil particles changes, which affects the microscopic composite structure of the soil, resulting in expansion of and strength deterioration of soil after water absorption. It can be seen that the macroscopic water absorption, expansion, and softening of unsaturated expansive soil depend not only on the content of clay minerals in the soil but also on the initial water content of soil and the combination form between clay minerals and non-clay minerals, namely, the microscopic spatial structure.